A new double twinning mode in a cold-rolled Zr alloy. (2nd January 2019) - An, Xinglong; Ni, Song; Song, Min
ABSTRACT: A new double twinning mode { 10 1 ¯ 2 } − { 10 1 ¯ 1 } characterised by a 38° ⟨ 1 2 ¯ 10 ⟩  twin/matrix misorientation was observed in a cold-rolled Zr70 Ti30 alloy using transmission electron microscope (TEM). The P-Py, P-B and B-Py interfaces coexist in double twins and were identified at the atomic scale. The presence of a large number of steps (P-Py and P-B interfaces) along the twin boundaries led to the curvature and deviation of the double twin boundaries from the twinning planes in macroscale. It is proposed that the temperature increase during multi-pass rolling process activated the { 10 1 ¯ 1 } twinning in { 10 1 ¯ 2 } primary twins.